THE ROLE OF LOCAL WISDOM IN SUPPORTING POLICIES DEFORESTATION SUPERVISION IN LANGKAT REGENCY, NORTH SUMATRA - Simson Ginting; Bengkel Bengkel (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of this study was to find out how the role of local wisdom in supporting deforestation monitoring policies in Langkat Regency, North Sumatra. This research method is qualitative with purposive sampling and the informants are the Technical Implementation Unit of the Forest Management Unit (KPH) Region I Stabat and the people who live and live around the forest in Langkat Regency. Data collection techniques are interviews, observation, and documentation. The data was processed and analyzed as a whole and systematically. The results of this study indicate that the implementation of the the Undang-Undang Republik Indonesia Nomor 18 Tahun 2013 concerning Prevention and Eradication of Forest Destruction in the implementation of monitoring of deforestation in the Forestry Service of KPH Region I Stabat is still not in accordance with community expectations such as legal certainty, sustainable forest existence, management and utilization of forest products, capacity and coordination of law enforcement officers. The role of local wisdom in supporting deforestation policies in Langkat Regency is that the forest management carried out by the government has not fully accommodated the community based forest management pattern. Forestry policy is still oriented towards state-dominated forest management system. The state-based forest management pattern relies on the government as the main actor in forest management, which is then supported by large capital owners, while the position of the community (customary community) is in a determining position. Legally political; this policy is inseparable from the need for natural resources, especially in the forestry sector.